PENINGKATAN PENGETAHUAN KEPATUHAN MINUM OBAT PESERTA ILP NOBOREJO MELALUI PENYULUHAN DI WILAYAH KERJA PUSKESMAS CEBONGAN - Aprilia, Lyla; Rofiana, Meilia; Samani, Ahmad Najib; Ulum, Apiatul; Erwiyani, Agitya Resti; Wijayanti, Estiningsih Sri (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
Patient compliance in taking medication greatly influences the success of a treatment. Low compliance with taking medication also occurs in elderly patients with a History of Chronic Diseases, so that many patients succumb to the disease and improve the patient’s quality of life. Chronic diseases have caused around 36 million deaths globally. Therefore, people with chronic diseases must control their condition regularly and take medication regularly to maintain the target of optimal disease improvement. The importance of increasing awareness of medication compliance, a community service was held entitled